Impact Resistance Behavior of Reinforced Concrete Beams Deteriorated due to Repeated Freezing and Thawing - Yusuke Kurihashi; Yoshinori Nonomura; Hisashi Konno (Shock and Vibration)
Many existing reinforced concrete (RC) structures constructed more than 50 years ago now require maintenance. This is especially true in cold, snowy regions where significant frost damage deterioration of RC structures becomes a severe problem. In this study, falling-weight impact tests were performed to investigate the impact resistance behavior of RC beams degraded by frost damage. An RC beam was subjected to approximately 900 freeze-thaw cycles to emulate the frost damage before the execution of the impact test. The surface of the beam was remarkably scaled, and its coarse aggregate was exposed. The degree of deterioration was evaluated by the distribution of ultrasonic propagation velocity. The following conclusions were drawn. (1) The ultrasonic propagation velocity of RC beams was significantly reduced following 872 freeze-thaw cycles. At the upper edge of the RC beam, the ultrasonic wave propagation velocity decreased from 4,000 m/s to 1,500 m/s in some parts. This corresponds to a relative dynamic elastic modulus of approximately 14%. (2) The residual deflection of RC beams with frost damage increased at most by 20% compared with beams without frost damage. The increase in residual deflection was primarily related to the peeling of concrete at the collision site and the opening of multiple bending cracks. (3) According to the existing residual deflection calculation formula, an increase of 20% in the residual deflection corresponds to a decrease of about 17% in the bending capacity of the RC beam. When the relationship between the degree of frost damage deterioration and the impact resistance of RC structures is defined, existing structures subjected to accidental impact force from rockfalls are safer and can be maintained more efficiently.